Pemanfaatan Limbah Kulit Kakao Sebagai Produk Bernilai Ekonomi di Desa Karang Baru : Pengabdian - Ayu Dwi Lestari; Intan Nur Fatma; Cintya Mayang Sari; Fathin Nazirah Aulia; Raudhatul Husna; Horia Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Cocoa pods are a byproduct of cocoa processing, abundant in quantity, but their utilization remains limited, potentially creating environmental problems. A community service program implemented in Karang Baru Village, Batu Bara Regency, aims to educate residents, particularly Family Welfare Movement (PKK) members, on how to process cocoa pods into marketable food products such as crackers and aci meatballs. This activity was carried out through field observations, outreach, and outreach on processing techniques. The results showed an increase in residents' insight and skills in utilizing cocoa pod waste, previously discarded or used as animal feed, into economically valuable products with the potential to be developed into home-based businesses. This innovation not only reduces the negative impact of agricultural waste on the environment but also opens up new business opportunities for the local community.